2023
DOI: 10.28991/esj-2023-07-02-09
|View full text |Cite
|
Sign up to set email alerts
|

Fusion Landsat-8 Thermal TIRS and OLI Datasets for Superior Monitoring and Change Detection using Remote Sensing

Abstract: Currently, updating the change detection (CD) of land use/land cover (LU/LC) geospatial information with high accuracy outcomes is important and very confusing with the different classification methods, datasets, satellite images, and ancillary dataset types available. However, using just the low spatial resolution visible bands of the remotely sensed images will not provide good information with high accuracy. Remotely sensed thermal data contains very valuable information to monitor and investigate the CD of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(8 citation statements)
references
References 43 publications
(59 reference statements)
1
7
0
Order By: Relevance
“…Similar results can be found in [25]. Yang et al [26] revealed that the SWAP index, combined with the multi-threshold run theory enables a more accurate identification of DFAA events in the Yangtze River basin [27][28][29]. The study found that the SPI and SPEI have strong monitoring ability for drought in the southern part of northern China.…”
Section: Introductionsupporting
confidence: 74%
“…Similar results can be found in [25]. Yang et al [26] revealed that the SWAP index, combined with the multi-threshold run theory enables a more accurate identification of DFAA events in the Yangtze River basin [27][28][29]. The study found that the SPI and SPEI have strong monitoring ability for drought in the southern part of northern China.…”
Section: Introductionsupporting
confidence: 74%
“…Based on the aforementioned process, the interpreted satellite image results were then validated for accuracy using statistical methods, employing the Overall Accuracy method as per Equation 4 and the Kappa coefficient as per Equation 5 [25], respectively.…”
Section: Figure 2 the Conception Frameworkmentioning
confidence: 99%
“…Employing Grim Schmidt spectral analysis on thermal satellite data, surpassing MH. This study refines the CD method for precise LU/LC pattern calculation (24). Study assesses optimal LU/LC mapping in Serdang, Selangor, Malaysia, comparing spatial resolutions (UAV, WorldView-2, Sentinel-2) with GS and Brovey algorithms for accuracy (25).…”
Section: Introductionmentioning
confidence: 98%